2021
DOI: 10.1088/1674-1056/abb3f5
|View full text |Cite
|
Sign up to set email alerts
|

A new heuristics model of simulating pedestrian dynamics based on Voronoi diagram*

Abstract: A new heuristics model based on the Voronoi diagram is presented to simulate pedestrian dynamics with the non-crowded state, in which these mechanisms of preference demand evading and surpassing, microscopic anti-deadlock, and site-fine-tuning are considered. The preference demand describes the willingness determination of detouring or following other pedestrians. In the evading and surpassing mechanisms, in order to achieve a balance between avoiding conflicts and minimizing detour distances, a new pair of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Another simulation study from the same first author modelled a mixed exit selection strategy in a multi-exit scenario, and found that there is a critical density to distinguish whether a pedestrian jam occurs in the evacuation and whether an exit selection strategy is in effect. [14] Wu et al [15] introduced a heuristic model based on the Voronoi diagram and successfully reproduced some typical phenomena. Jia et al [16] used the social force model approach and found that the evading and surpassing behavior increases the evacuation time, but that a circle-shaped obstacle induces a relatively higher bottleneck passing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Another simulation study from the same first author modelled a mixed exit selection strategy in a multi-exit scenario, and found that there is a critical density to distinguish whether a pedestrian jam occurs in the evacuation and whether an exit selection strategy is in effect. [14] Wu et al [15] introduced a heuristic model based on the Voronoi diagram and successfully reproduced some typical phenomena. Jia et al [16] used the social force model approach and found that the evading and surpassing behavior increases the evacuation time, but that a circle-shaped obstacle induces a relatively higher bottleneck passing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the good performance and simple rules, the heuristics-based model has attracted increasing attention in recent years. [21][22][23][24][25][26] Although the model has been widely applied, there remain deficiencies in theory and also in practical applications. To overcome the deficiency that the original heuristics-based model fails to reproduce lane formation in the dense crowds, Guo et al [27] proposed an improved model by modifying the objective function of the target direction.…”
Section: Introductionmentioning
confidence: 99%